Physical Environment and Food Safety on Loyalty through Customer Satisfaction at Fast Food Restaurant “X” in North Jakarta - Rodhiah Rodhiah; Lerbin R Aritonang R; Ervina Ervina (International Journal of Management Science and Application, 2024)
The market potential for fast food restaurants in Indonesia is large. Fast food restaurant “X” in North Jakarta which is one of the fast food restaurants in Indonesia has four competitors that becomes a challenge. Therefore, this fast food restaurant can build good relationships with customers, so customer loyalty can be achieved. Customer loyalty can be influenced by physical environment and food safety through customer satisfaction. Furthermore, customer loyalty can be influenced by customer satisfaction. Customer satisfaction can be influenced by physical environment and food safety. Thus, this research aims to test the influence of physical environment and food safety on customer satisfaction; test the influence of customer satisfaction on customer loyalty; and examine the role of customer satisfaction in mediating the influence of physical environment and food safety on customer loyalty. The study population is customers from fast food restaurant “X” in North Jakarta. 140 people as the research respondents were examined. The sampling method used is non-probability with purposive sampling technique. The research instruments used are questionnaires via Google Form. The data analysis technique used is SEM using SmartPLS software. The results are physical environment and food safety have positive influence on customer satisfaction, customer satisfaction has positive influence on customer loyalty, and physical environment and food safety have positive influence on customer loyalty through customer satisfaction. Hence, fast food restaurant “X” in North Jakarta must pay attention to the physical environment and food safety because these can increase customer satisfaction and ultimately maintain customer loyalty.